Alkyne gem‐Hydrogenation: Formation of Pianostool Ruthenium Carbene Complexes and Analysis of Their Chemical Character. (17th May 2019) - Biberger, Tobias; Gordon, Christopher P.; Leutzsch, Markus; Peil, Sebastian; Guthertz, Alexandre; Copéret, Christophe; Fürstner, Alois
Abstract: Parahydrogen ( p ‐H2 ) induced polarization (PHIP) NMR spectroscopy showed that [Cp X Ru] complexes with greatly different electronic properties invariably engage propargyl alcohol derivatives into gem ‐hydrogenation with formation of pianostool ruthenium carbenes; in so doing, less electron rich Cp X rings lower the barriers, stabilize the resulting complexes and hence provide opportunities for harnessing genuine carbene reactivity. The chemical character of the resulting ruthenium complexes was studied by DFT‐assisted analysis of the chemical shift tensors determined by solid‐state 13 C NMR spectroscopy. The combined experimental and computational data draw the portrait of a family of ruthenium carbenes that amalgamate purely electrophilic behavior with characteristics more befitting metathesis‐active Grubbs‐type catalysts. Abstract : Porträtierend : Schwach elektronenschiebende Cyclopentadienyl(Cp X )‐Liganden senken die Barriere für die unorthodoxe gem ‐Hydrierung von Alkinen durch [Cp X Ru]‐Komplexe und stabilisieren kinetisch die entstehenden Pianostool‐Rutheniumcarbene. Die aus 13 C‐NMR‐Festkörperspektren extrahierten chemischen Verschiebungstensoren zeichnen das Porträt elektrophiler Fischer‐Carbene mit einer an Grubbs‐Katalysatoren erinnernden Note.